The Analysis of Science Literacy Competencies Ability on Digestive System Material of Eleventh Grade Students in SMAN 1 Bangsri Jepara - Hazuwa, Nasyatal Ula Hawa; Harini, Nugrahaningsih Wahyu (FMIPA UNNES, 2021)
The research aims to analyze the student scientific literacy competence abilities in 11th grade SMAN 1 Bangsri Jepara on the digestive system material and the factors that influence it. The research method uses quantitative descriptive with survey techniques. The sample was 143 science students of 11th grade SMAN 1 Bangsri Jepara in the 2020/2021 academic year. Instruments are science literacy competence test totaling 30 multiple choice and questionnaire for student responses related to learning. The results of students scientific literacy competence ability in SMAN 1 Bangsri Jepara on the digestive system material were overall good. Students are able to remember, apply scientific knowledge; explain the implications of the article; identify and produce explanatory models; ensure objectivity, analyze, describe, and infer data; evaluate and propose ways of scientific investigation; identify problems, assumptions, arguments and scientific evidence. However, the ability of students is still lacking in determining the right predictions; propose a hypothesis; and evaluating descriptions from different sources.The factors that affect students scientific literacy competence are, learning models, teaching materials, evaluation questions, and practicum on the digestive system material.